Female paraurethral leiomyoma: a case report and literature review - Permata, Veryne Ayu; Wibowo, Syaeful Agung; Wijanarko, Suharto; Liana, Nisa Anestesia; Insan, Yudhistya Ngudi; Darto; Anggraeni, Asih (International Surgery Journal, 2025)
Urethral myoma is an uncommon benign tumor of mesenchymal origin. Establishing the diagnosis can be challenging due to its similarity to other periurethral masses. We report a case of a 36-year-old multiparous woman (P4A0) presenting with a painless mass protruding from the distal vaginal wall, surpassing the vaginal introitus for the past two years. Physical examination revealed a round, solid mass measuring 9.4 x 4 x 4 cm emerging from the vagina. A trans perineal scan indicated a leiomyoma in the anterior vaginal area. The mass was successfully excised via a vaginal approach in collaboration with a urologist. A Foley catheter was placed preoperatively, and the patient showed favorable recovery three weeks post-surgery. Histopathological analysis confirmed the diagnosis of leiomyoma. Urethral myoma accounts for approximately 5% of leiomyoma cases. Preoperative imaging and thorough clinical examination are essential for diagnosis. The preferred treatment is complete surgical excision via the vaginal route, followed by histological evaluation. While laparoscopic management has been reported in isolated cases, local recurrence remains rare. Close postoperative monitoring can help detect potential recurrences at an early stage. This case highlights the rarity of urethral leiomyoma and its successful management through surgical intervention.